2015
DOI: 10.1016/j.neuropharm.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Glycine transporter 1 is a target for the treatment of epilepsy

Abstract: Glycine is the major inhibitory neurotransmitter in brainstem and spinal cord, whereas in hippocampus glycine exerts dual modulatory roles on strychnine-sensitive glycine receptors and on the strychnine-insensitive glycineB site of the N-methyl-D-aspartate receptor (NMDAR). In hippocampus, the synaptic availability of glycine is largely under control of glycine transporter 1 (GlyT1). Since epilepsy is a disorder of disrupted network homeostasis affecting the equilibrium of various neurotransmitters and neuromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…This increase in astrocyte Na + can have a dual effect, since it may increase NMDA receptor mediated excitation, but at higher concentrations it can also induce an inhibitory effect mediated by glycine receptor activation. Glyt1 blockade was recently shown to inhibit epileptic activity (Shen et al, ) suggesting that elevated extracellular glycine levels may overall inhibit seizures. Finally, Na + increase in astrocytes can trigger the reversal of the Na + /Ca 2+ exchanger, effectively allowing Ca 2+ to enter the astrocyte (Kirischuk et al, ), thereby linking Na + entry to the Ca 2+ ‐dependent mechanisms.…”
Section: Epilepsymentioning
confidence: 99%
“…This increase in astrocyte Na + can have a dual effect, since it may increase NMDA receptor mediated excitation, but at higher concentrations it can also induce an inhibitory effect mediated by glycine receptor activation. Glyt1 blockade was recently shown to inhibit epileptic activity (Shen et al, ) suggesting that elevated extracellular glycine levels may overall inhibit seizures. Finally, Na + increase in astrocytes can trigger the reversal of the Na + /Ca 2+ exchanger, effectively allowing Ca 2+ to enter the astrocyte (Kirischuk et al, ), thereby linking Na + entry to the Ca 2+ ‐dependent mechanisms.…”
Section: Epilepsymentioning
confidence: 99%
“…In addition, the mechanism underlying epilepsies-mediated injury remains to be investigated. Our previous study investigated severe neuronal injury, damage to the blood-brain barrier (BBB) and neuronal uptake of serum albumin in the brain parenchyma of a kainic acid (KA)-induced rat model of temporal lobe epilepsy (TLE) (7,8). The present study aimed to investigate the pathological changes and underlying mechanisms of spinal cord injury in TLE.…”
Section: Spinal Cord Injury and Its Underlying Mechanismmentioning
confidence: 99%
“…Another previous study showed that after seizure, the expression levels of serum C-response protein, cytokines and inflammatory factors are markedly increased, thus indicating a systemic seizure-associated inflammatory reaction (6). The brain and spinal cord share a common origin, which is supported by the co-expression of specific neurotransmitters in both locations (7,8). Therefore, there may be a close connection between spinal cord injury and the abnormal discharge of brain neurons (7,8).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Glyt1 blockade was recently shown to inhibit epileptic activity (Shen et al . ) suggesting that elevated extracellular glycine levels may overall inhibit epileptic activity. Finally, a Na + increase can trigger the reversal of the Na + /Ca 2+ exchanger effectively allowing Ca 2+ to enter the astrocyte (Kirischuk et al .…”
Section: Introductionmentioning
confidence: 99%